Retail Internationalization in Emerging Countries The Positioning of Global Retail Brands in China - Pennemann, Karin. (Reihe Handel und Internationales Marketing / Series Retailing and International Marketing, 2013)
Retail firms have internationalized aggressively, first into developed countries and then into developing countries. Doing business in emerging countries offers growth opportunities, but also holds some uncertainties due to the lack of knowledge on whether international retailers can succeed with a global brand in business that was originally local. To expand on this issue, Karin Pennemann discusses successful positioning options for retail brands in the context of emerging countries and draws implications for retailers<U+0019> international brand management. Her research identifies the importance of perceived brand globalness, the underlying value creation process, and the relevance of cultural differences in international retail brand management. Contents ʺ Internationalization of Retail Firms in Emerging Countries ʺ Meaning, Importance, and Value Creation Process of Perceived Brand Globalness as a Retailer<U+0019>s Tool for Success in Emerging Countries ʺ International Retail Brand Management Target Groups ʺ Academics and students of business administration with a focus on international marketing and management ʺ Managers of retail and service firms, as well as international marketing managers The Author Dr. Karin Pennemann gained her doctoral degree at the Institute for Marketing and Retailing of Trier University. Her work was acknowledged by the American Marketing Association. She works in the strategy development department of a leading international company. The Editors The series Handel und Internationales Marketing/Retailing and International Marketing is edited by Prof. Dr. Bernhard Swoboda and Prof. Dr. Thomas Foscht.